EFEKTIVITAS PELAKSANAAN PEMBINAAN TERHADAP NARAPIDANA PENGEDAR NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS II B PAYAKUMBUH - Anny Yuserlina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Guidance and mentoring of prisoners includes coaching and guidance programs in the form of personality development activities and independence development activities. Personality development is directed at mental and character development so that prisoners become fully human, devoted and responsible to themselves, their families, and society. Meanwhile, the development of independence is directed at fostering talents and skills so that prisoners can return to their roles as free and responsible members of society. In solving problems and achieving these goals, the approach method used is the empirical juridical approach. The results of the study found that the guidance provided by the Class IIB Payakumbuh correctional institution for prisoners who committed acts of narcotics abuse. This is reflected in the fact that the data in the field or the data in the institution can be concluded that since the establishment of the Payakumbuh Class IIB prison, it has been implemented or has been given to inmates but has not been maximized and there is no difference in coaching for narcotics trafficker prisoners with other inmates in Class IIB prisons. Payakumbuh. 2. The obstacles faced in the implementation of the development of narcotics trafficker prisoners are the lack of awareness of the prisoners themselves, the lack of human resources for officers, overload, lack of facilities and infrastructure in the institution. 3. Efforts that need to be made are increasing the number of officers, increasing human resources of officers by conducting training or socialization from the government and also the institutions to be more open to the public or NGOs, journalists or social media so that the outside world knows what are the obstacles to the parties. Institutions in providing coaching. And the most important thing is to improve the quality of coaching and coaching programs that are carried out.